Methylmercury Cycling at the Aquatic-terrestrial Interface in a High Arctic Freshwater Continuum - Varty, Stephanie (2019)
Methylmercury (MeHg) is a global toxin which bioaccumulates and biomagnifies through food webs. To discern how MeHg enters Arctic food webs, it is important to understand spatial and seasonal cycling of MeHg at the terrestrial-aquatic interface, processes which are sensitive to climate change. This research determined hotspots of MeHg production and degradation in a High Arctic freshwater continuum, and how these processes varied between ice-on and ice-off conditions. Different compartments of the Skeleton Continuum of Lake Hazen, Nunavut were sampled to capture variation in MeHg production and degradation. Examining interconnectedness of the landscape revealed that production hotspots occur in multiple compartments (lake/pond sediments, pore water), yet downstream degradation hotspots and storage (lake water, wetland soils) prevent MeHg from entering the downstream system. Additionally, high MeHg concentrations found in the springtime (water column, snow) solidify the theory that spring freshet is an important source of MeHg to freshwater systems. M.Sc.